2021
DOI: 10.7883/yoken.jjid.2020.781
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Clinical and Laboratory Features and Treatment Options of 237 Symptomatic and Asymptomatic Children Infected with SARS-CoV-2 in the Early Phase of the COVID-19 Pandemic in Turkey

Abstract: Japanese Journal of Infectious Diseases Comparison of clinical and laboratory features and treatment options of 237 symptomatic and asymptomatic children infected with SARS-CoV-2 in the early phase of the COVID-19 pandemic in Turkey

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…These studies included a total of 104,058 laboratory-confirmed COVID-19 cases, of which 25,050 exhibited no symptoms at the time of testing and 7,220 remained asymptomatic. We identified 170 studies that reported asymptomatic infections ( 11 13 , 17 183 ), 332 studies that reported silent infections at the time of testing ( 10 12 , 14 , 17 20 , 23 27 , 31 , 32 , 35 40 , 42 44 , 46 , 47 , 49 , 50 , 52 , 53 , 56 58 , 60 66 , 68 , 69 , 73 75 , 77 79 , 81 , 84 , 87 , 90 94 , 97 , 99 , 101 , 103 , 104 , 106 , 111 , 113 116 , 118 , 119 , 121 123 , 125 , 127 , 128 , …”
Section: Resultsmentioning
confidence: 99%
“…These studies included a total of 104,058 laboratory-confirmed COVID-19 cases, of which 25,050 exhibited no symptoms at the time of testing and 7,220 remained asymptomatic. We identified 170 studies that reported asymptomatic infections ( 11 13 , 17 183 ), 332 studies that reported silent infections at the time of testing ( 10 12 , 14 , 17 20 , 23 27 , 31 , 32 , 35 40 , 42 44 , 46 , 47 , 49 , 50 , 52 , 53 , 56 58 , 60 66 , 68 , 69 , 73 75 , 77 79 , 81 , 84 , 87 , 90 94 , 97 , 99 , 101 , 103 , 104 , 106 , 111 , 113 116 , 118 , 119 , 121 123 , 125 , 127 , 128 , …”
Section: Resultsmentioning
confidence: 99%
“…After screening by title and abstract, 246 articles proceeded to full-text review. Following full-text review, 126 articles, which reported on a total of 48,332 patients, were included for data extraction and analysis 25–148. The PRIMSA flow diagram is provided in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…The ratio of asymptomatic patients to the patient population in our study is similar to that in larger series. 8 T wave shows ventricular repolarization. Transmyocardial parameters are measurements based on the T wave.…”
Section: Discussionmentioning
confidence: 99%